Kerentanan DAS Kali Bekasi ditinjau dari aspek sosial-ekonomi-kelembagaan - Kunandar Prasetyo; Gatot Prayoga; Andrian Rizaldy Azhar; Tri Permadi; Dewanti Pratiwi (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2020)
Watershed sustainability is influenced by socio-economic conditions, behavior patterns and management levels closely related to institutional arrangements. Problems in watershed management can be minimized by knowing the social, economic and institutional conditions in the area. This study aimed to identify the level of social, economic and institutional vulnerability of the community, which can be considered in Bekasi River watershed management. Vulnerability analysis was carried out on three criteria: (1) Social criteria, including population pressure, culture and traditional values. (2) Economic criteria, namely dependence on land seen from the dominant economic sector, and (3) Institutional criteria, namely the empowerment of formal and informal institutions in conservation activities. The results showed that the Bekasi River watershed vulnerability level in social criteria (population density and traditional values parameters) was very high, while conservation behavior was not vulnerable. In the economic aspect, most sub-districts in the Bekasi River watershed had a moderate vulnerability level, as they were dominated by the service sector as the primary economic sector. The institutional aspect was not vulnerable because formal and informal institutions play an active role in the watershed conservation activities, such as bamboo tourism development and climate village program.